2022
DOI: 10.3390/nu14214666
|View full text |Cite
|
Sign up to set email alerts
|

Essential Fatty Acid Deficiency in Cystic Fibrosis Disease Progression: Role of Genotype and Sex

Abstract: Adequate intake of nutrients such as essential fatty acids (EFA) are critical in cystic fibrosis (CF). The clinical course of deterioration of lung function in people with CF has been shown to relate to nutrition. Independent of the higher energy consumption and malabsorption due to pancreatic insufficiency, EFA deficiency is closely associated with the risk of pulmonary infection, the most significant pathology in CF. This review will focus on the EFA deficiency identified in people with CF, as well as the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 64 publications
(74 reference statements)
2
6
0
Order By: Relevance
“…However, our data align with previously published studies suggesting there is a dysregulation of linoleic acid metabolism, indicated by increased metabolites in CP, 53 or a reduction in linoleic acid absorption, and an increased de novo lipogenesis in CP and changes of FA composition, including linoleic acid, in diabetes and CP 6,8 . Unexpectedly, we did not observe any differences in FA composition in CP with and without EPD, often seen in patients with cystic fibrosis-associated pancreatitis 54 . Although this study did not have subjects with cystic fibrosis or hyperlipidemia, a future study including these additional forms of pancreatic disease would further determine if our findings can also apply to these subsets of patients.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, our data align with previously published studies suggesting there is a dysregulation of linoleic acid metabolism, indicated by increased metabolites in CP, 53 or a reduction in linoleic acid absorption, and an increased de novo lipogenesis in CP and changes of FA composition, including linoleic acid, in diabetes and CP 6,8 . Unexpectedly, we did not observe any differences in FA composition in CP with and without EPD, often seen in patients with cystic fibrosis-associated pancreatitis 54 . Although this study did not have subjects with cystic fibrosis or hyperlipidemia, a future study including these additional forms of pancreatic disease would further determine if our findings can also apply to these subsets of patients.…”
Section: Discussionsupporting
confidence: 92%
“…6,8 Unexpectedly, we did not observe any differences in FA composition in CP with and without EPD, often seen in patients with cystic fibrosis-associated pancreatitis. 54 Although this study did not have subjects with cystic fibrosis or hyperlipidemia, a future study including these additional forms of pancreatic disease would further determine if our findings can also apply to these subsets of patients.…”
Section: Discussionmentioning
confidence: 95%
“…Various CFTR variants related with fatty acid metabolism abnormalities have been reported in CF, such as an abnormally high arachidonic acid (AA) to docosahexaenoic acid (DHA) ratio and a linoleic acid (LA) deficiency, which is directly related to the severity of the CFTR variants [11,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Adequate nutrition, including the intake of essential fatty acids (EFAs), particularly omega-3 and omega-6 polyunsaturated fatty acids (n-3 and n-6 PUFAs), is essential in patients with cystic fibrosis (CF) because of the high incidence of EFA deficiency and the role played by this deficiency in fat malabsorption and symptoms and the progression of pulmonary disease [1,2]. Although the prognosis of CF has remarkably improved with the introduction of modulators to target the specific mutations of the cystic fibrosis transmembrane conductance regulator (CFTR) gene [3], there has been limited progress in defining the underlying mechanisms involved in altered EFA metabolic pathways [4,5] and the anti-inflammatory effect of the dietary modulation of EFA deficiency [6,7].…”
Section: Introductionmentioning
confidence: 99%